Sistema Háptico de Detección de Obstáculos para invidentes (2021)
Blindness is a sensory disability that affects the ability of the eyeballs to perceive light, its multiple shades and forms of emission "images". This disability hinders the mobility of those who suffer from it, due to the current infrastructure of cities and interiors, and the fact that most mobility solutions that are in the form of personal accessories have limitations due to their detection approach oriented to people. existing obstacles at ground level; For this reason, the main design approach was that of a system that could inform the user about the obstacles that the upper limbs of the human body are targeting. The prototype is implemented in a hat-shaped structure that has 6 proximity sensors (3 infrared "IR" and 3 ultrasonic "US") located in pairs on the front brim of the hat (IR, US); These pairs of sensors will point towards the front, but in different directions (left, front, right), having a differential angle of 15% with respect to the front pair; in this way, obtain information from multiple points of the surveyed area. After the census and data collection, the author's algorithm will process and eliminate the measurements that it identifies as noise with a maximum tolerance rate of 25% noise for ultrasonics and 20% for infrared, later, the prototype will characterize the processed data using individual Look Up Tables for each sensor, obtained by implementing a prediction model in the MATLAB program. The system will finally inform of the presence and proximity of an obstacle by means of a haptic bracelet made up of 3 vibrotactile motors, which will work one after the other, and which will have specific stimuli programmed that the user will interpret, since each motor represents a direction from which they can come. the obstacles; said obstacles detected are in a range of 20cm to 79cm.